(untitled) (Scientific journal of the Fergana State University, 2025)
The main purpose of using modern technologies and methods by each teacher during lessons is to form knowledge and skills in subjects, as well as to deepen and strengthen their knowledge in the field of mastering subjects that will be the focus of attention. their interests.